First report of Nattrassia mangiferae as a postharvest fungal pathogen of white yam (Dioscorea rotundata) in Nigeria - Sangoyomi, T.; Ekpo, E.; Asiedu, Robert (Scientific Societies, 2002)
A survey of the yam growing areas of Nigeria was conducted in January 1999 to identify the major fungal pathogens responsible for considerable tuber rot losses in storage. A total of 150 tubers of white yam showing rot symptoms were collected from 30 barns at 18 locations spanning three agroecologies (guinea savanna, forest/savanna transition, and forest) within the yam belt of Nigeria. Tuber pieces were cut at the interface between healthy and infected tissue, surface-sterilized in 10% bleach solution (0.05% sodium hypochlorite), rinsed in sterile distilled water, and plated on potato dextrose agar (PDA; Difco Laboratories, Detroit, MI) amended with lactic acid (1ml/liter) to reduce bacterial contamination. Cultures were incubated at 28°C for 4 days. Isolations from the guinea savanna agroecology showed that Nattrassia mangiferae Sutton & Dyko (synonym Hendersonula toruloidea) (3) had 42% frequency of occurence, Botryodiplodia theobromae Pat. (10%), Penicillium oxalicum Curie & Thom. (12%), and Aspergillus niger Tiegh. had 50% frequency of occurrence of the total fungi isolated from this region. In the forest/savanna transition agroecology, N. mangiferae had 28% frequency of occurrence, while B. theobromae, P. oxalicum, and A. niger had 10, 14, and 50% frequency of occurrence, respectively. In the forest agroecology, N. mangiferae and B. theobromae had 6% frequency of occurrence, while P. oxalicum and A. niger had 17 and 72% frequency of occurrence, respectively. N. mangiferae was more frequent in occurrence than the two known major fungal pathogens (B. theobromae and P. oxalicum) of yam tuber in storage. Hence, its pathogenicity was tested on healthy tubers. Fifteen healthy tubers were wounded and inoculated individually with 7-day-old mycelial plugs of each of 10 isolates of N. mangiferae from each agroecology using the cork borer technique (2), placed in polythene bags, and stored in a barn for 14 days at 27± 2°C. Control tubers were inoculated with sterile agar plugs. Tubers were sliced at the points of inoculation, and lesion development was measured. N. mangiferae was found to be pathogenic in yam tubers causing soft, wet, brown rots similar to those observed in natural infections, and it appeared as dark necrotic lesions on tuber surface. In culture however, colonies are fluffy with olivaceous gray coloration that gradually darkens as the fungus matures. The fungus grows rapidly on PDA and is able to attain a radial diameter of 90 mm by the fourth day after inoculation. Cultures reisolated from the inoculated tubers matched those used for inoculation. Isolates obtained from the forest/savanna transition agroecology caused significantly (P < 0.05) larger rot lesions (24.67mm) than those obtained from the guinea savanna (18.33mm), and the forest (21.67mm). In another experiment, tubers were inoculated with N. mangiferae without wounding the tubers (mycelial disks were firmly placed on the tuber surface to make adequate contact), and the control tubers were inoculated with sterile agar plugs. Tubers inoculated without wounding remained asymptomatic when assessed for rot development. N. mangiferae has been reported as a root and stem rot pathogen of cassava in West Africa (1). To our knowledge, this is the first report of N. mangiferae causing tuber rot of yams in storage.References: (1) W. Msikita et al. Plant Dis. 81:1332, 1997. (2) N. Okafor Exp. Agric. 2:179, 1966. (3) B. C. Sutton and B. J. Dyko. Mycol. Res. 93:466, 1989.